Low water availability increases susceptibility to peanut smut (Thecaphora frezzii) in peanut crop - Paredes, Juan Andrés; Guzzo, María Carla; Monguillot, Joaquín Humberto; Asinari, Florencia; Posada, Gisella A.; Oddino, Claudio M.; Giordano, Damian F.; Morichetti, Sergio A.; Torres, Adriana M.; Rago, Alejandro Mario; Monteoliva, Mariela Ines (Wiley, 2023)
Peanut smut (causal agent Thecaphora frezzii) and seasonal drought are the two main factors reducing peanut yields in Argentina. There are no previous studies about the effect of drought on peanut smut occurrence. We evaluated the effect of soil water limitation on smut symptoms in greenhouse and field assays. Additionally, we analysed the biochemical responses of plants to the combined stress caused by water limitation and smut infection in greenhouse experiments. We found that a moderate water deficit (30% of soil water-holding capacity) increased smut symptoms and differentially increased proline and reduced chlorophylls in the host. Subsequently, we studied the correlation between field precipitation data and smut damage from 2015 to 2020 in naturally infected fields with a high T. frezzii spore load in the soils. Strong correlations between precipitation and severely affected pods, severity disease index and incidence were found from January to March (susceptibility window for T. frezzii infections). We suggest a strategy of irrigation in a specific time frame to mitigate smut damage when there is a water deficit in the growing season.